Evaluación de Cuatro Métodos de Germinación en dos Especies Nativas de Interés Ambiental en el Vivero del Campus Salache –UTC. - Monta Eres, Gabriela Nathaly (2019)
The main objective of this project is to evaluate four germination methods in two native species of environmental interest in the nursery of the Salache Campus - UTC; The species under study are the arrayan (Myrcianthes Hallil) and guarango (Caesalpinia spinosa). The experimental design used to apply a CRD (Completely Random Design) was completely randomized with a factorial arrangement (3 x 2) plus 2 controls, determining the coefficient of variation and the separation of measurements according to Tukey at 5%. Two factors were applied to the study. Factor A native species: arrayan and guarango. Factor B germination methods: physical method, a mechanical method, chemical method, traditional method. The variables to be evaluated were: days of emergence, the percentage of germination, height of the plant from 15 days to 90 days. From the results obtained the analysis of variance for the variable, days of emergency, statistical significance is established for the treatments. The coefficient of variation is 6.42% with an average of 47.32 days. The results of the ADEVA establish the difference between the germinative treatments in the application to the seed: physical method, a mechanical method, chemical method in different percentages. In the variable percentage of germination of the species it was determined that the best germination method in the arrayan (Myrcianthes Hallil) was the mechanical method (e1m2) with 51.4% and in the guarango (Caesalpinia spinosa) the chemical method (e2m3) with 58.30% germination of their seeds. In the variable height of the plant at 90 days, the best method of germination in the arrayán (Myrcianthes Hallil) is the mechanical method (e1m2) with a height of 4cm and in the guarango (Caesalpinia spinosa) the chemical method (e2m3) with 4.76cm of height